2013
DOI: 10.4319/lom.2013.11.382
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of rapid, semi‐automated assessment of plankton abundance, biomass, and growth rate estimates: Coulter Counter versus light microscope measurements

Abstract: Here we determined (1) how accurately the semi‐automated Coulter Counter (CC) measured the abundance, volume, and growth rates of mono‐specific plankton cultures compared to light microscopy and (2) whether CC‐derived particle size‐abundance spectra of whole water samples provided a near‐real time assessment of plankton community composition. A significant, positive relationship was found between CC particle and microscope cell abundance and volume estimates for 16 phylogenetically diverse plankton species. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Grazing by A.clausii on long and short chains was calculated from measured Skeletonema biovolume with a Beckman Coulter Multisizer III. Using biovolume we avoid a biased estimate due to different particle size in the cultures (Kim and Menden-Deuer, 2013). Clearance rate (F, ml ind -1 day -1 ) was calculated with a modified equation by Frost (Frost, 1972):…”
Section: Grazing Ratesmentioning
confidence: 99%
“…Grazing by A.clausii on long and short chains was calculated from measured Skeletonema biovolume with a Beckman Coulter Multisizer III. Using biovolume we avoid a biased estimate due to different particle size in the cultures (Kim and Menden-Deuer, 2013). Clearance rate (F, ml ind -1 day -1 ) was calculated with a modified equation by Frost (Frost, 1972):…”
Section: Grazing Ratesmentioning
confidence: 99%
“…including tolerance of environmental conditions [16], elemental composition [17] and growth rate [18]. A comprehensive study of intra-strain variability in one phytoplankton species showed distinguishing characteristics in cell size, maximum growth and photosynthesis rates, tolerance of low salinities, resource use and toxicity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Grazer and phytoplankton prey abundance and cell size were monitored using a Multisizer TM 3 Coulter counter (version 3.53; Beckman Coulter, Indianapolis, IN, USA). The Coulter counter provided a more rapid and reliable sampling approach than microscopy and allowed convenient monitoring of the cultures over the course of the experiments (Kim & Menden-Deuer, 2013). Grazer and phytoplankton prey were easily distinguishable on the Coulter counter based on their respective size distributions.…”
Section: Methodsmentioning
confidence: 99%